Cardiovascular Disease After Hysterectomy in the Nurses' Health Study and Nurses' Health Study II - Thao, Viengneesee; Borah, Bijan; Stewart, Elizabeth A; Farland, Leslie V; Laughlin-Tommaso, Shannon K; Khan, Zaraq; Coutinho, Thais D; Rassier, Sarah L Cohen (Obstetrics and gynecology (New York. 1953), 2025)
To examine long-term risk of cardiovascular disease (CVD) after undergoing hysterectomy with or without oophorectomy. Participants in the Nurses' Health Study (NHS) and the Nurses' Health Study II (NHS II) (N=239,907) were grouped based on history of no surgery, hysterectomy alone, or hysterectomy with bilateral oophorectomy, and further categorized by use or nonuse of estrogen. The primary outcome was the risk of CVD (combined incidence of fatal and nonfatal myocardial infarction, coronary artery bypass graft and stroke) among the groups. Data were analyzed by multivariable Cox proportional hazards model, stratified by age to estimate adjusted hazard ratios (aHRs). Models controlled for menopausal hormone therapy as well as race, marital status, family income, personal and family history of relevant health conditions, alcohol consumption, physical activity, healthy eating index, body mass index (BMI), and parity. After pooling the NHS and NHS II participants, the risk of CVD was higher among all participants who had hysterectomy before age 50 years compared with no surgery. Specifically, those who underwent hysterectomy before age 46 years and did not use estrogen had a 21.0% increased risk of CVD compared with no surgery (aHR 1.21, 95% CI, 1.04-1.40). Furthermore, among estrogen users who had hysterectomy and bilateral oophorectomy, those from the youngest two age groups (younger than 46 years and 46-50 years) had higher risk of CVD (aHR 1.26, 95% CI, 1.16-1.37; aHR 1.11, 95% CI, 1.01-1.22, respectively) compared with no surgery. Non-estrogen users who had hysterectomy with bilateral oophorectomy from all but the oldest age group (older than 60 years) experienced higher risk of CVD compared with no surgery. Younger age at time of hysterectomy, with or without oophorectomy, is associated with higher risk of CVD. Notably, use of estrogen does not appear to mitigate deleterious effects of hysterectomy with oophorectomy before age 50 years.